Aligning vertical interventions to health systems: a case study of the HIV monitoring and evaluation system in South Africa - Kawonga Mary; Blaauw Duane; Fonn Sharon (BMC, 2012)
Abstract Background Like many low- and middle-income countries, South Africa established a dedicated HIV monitoring and evaluation (M&E) system to track the national response to HIV/AIDS. Its implementation in the public health sector has however not been assessed. Since responsibility for health services management lies at the district (sub-national) level, this study aimed to assess the extent to which the HIV M&E system is integrated with the overall health system M&E function at district level. This study describes implementation of the HIV M&E system, determines the extent to which it is integrated with the district health information system (DHIS), and evaluates factors influencing HIV M&E integration. Methods The study was conducted in one health district in South Africa. Data were collected through key informant interviews with programme and health facility managers and review of M&E records at health facilities providing HIV services. Data analysis assessed the extent to which processes for HIV data collection, collation, analysis and reporting were integrated with the DHIS. Results The HIV M&E system is top-down, over-sized, and captures a significant amount of energy and resources to primarily generate antiretroviral treatment (ART) indicators. Processes for producing HIV prevention indicators are integrated with the DHIS. However processes for the production of HIV treatment indicators by-pass the DHIS and ART indicators are not disseminated to district health managers. Specific reporting requirements linked to ear-marked funding, politically-driven imperatives, and mistrust of DHIS capacity are key drivers of this silo approach. Conclusions Parallel systems that bypass the DHIS represent a missed opportunity to strengthen system-wide M&E capacity. Integrating HIV M&E (staff, systems and process) into the health system M&E function would mobilise ear-marked HIV funding towards improving DHIS capacity to produce quality and timely HIV indicators that would benefit both programme and health system M&E functions. This offers a practical way of maximising programme-system synergies and translating the health system strengthening intents of existing HIV policies into tangible action.